PENGEMBANGAN SENSITIFITAS DAN KREATIFITAS GURU BAHASA INGGRIS DALAM PENERAPAN METODE PEMBELAJARAN: ANALISIS METODE PENGAJARAN BAHASA INGGRIS BERBASIS TUGAS - Berlin Sibarani (BAHAS, 2009)
Sensitivity refers to the teacher’s ability to find out instantly if learning has happened or not during the process of teaching and learning a second language while creativity to the ability to create improving teaching behaviors to overcome the learning failure happening during the teaching and learning activities. These competencies are very important and considered a key factor of effective teaching. Therefore they badly need to be developed. To develop these competencies, many related teaching variables must be mastered and one of these variables is language teaching method.  For the purpose of sensitivity and creativity development, a language teaching method should be correctly studied by studying its linguistic assumption and its learning principle thoroughly rather than by simply memorizing the methodological procedures proposed by a method and putting them into action as exactly as prescribed. The latter is very far from sufficient. In studying the task-based language teaching for the same purpose, the concept of task and its underlying learning principle-which is the same as that underlying the learning of first language-should be comprehensively mastered. The mastery of a language teaching method in a correct way tends to be more contributive to the development of creativity in the method application rather than to the development of sensitivity.   Key Words: sensitivity, creativity, language teaching, task